When creativity meets systemic functional linguistics: The birth of an innovative 3D model. (28th May 2018) - Law, Locky
Abstract : As of today, the proportion of research in creativity which focuses on the description of language and language use has been minuscule, with Carter's (2004) creativity matrix for spoken English being arguably the most systematic attempt in over a decade. In spite of his success in identifying certain key features associated with creativity production, he too has acknowledged the presence of a rather significant gap in between those interpersonal features and context (of situation) and has thus called for a comprehensive model to fill this niche. The aim of this article is to address this issue by proposing a new descriptive model for the representation of the probabilistic nature of linguistic creativity using a systemic functional linguistic approach. This article is divided into four sections. The first section begins by describing the background and definitions of creativity. The second section discusses the main concepts and theories involved in the model construction. The third section provides a detailed, step-by-step walk-through of the model. Finally, the last section concludes with a short discussion of the advantages and limitations of this model.